In the spirit of wetlands : reviving habitat in the Illinois river watershed - Howard, Clare (Journalist) (3 Fields Books, an imprint of the University of Illinois Press, 2022)
"Individuals from all walks of life have devoted their time, energy, and money to restoring the state's lost wetlands. Clare Howard and David Zalaznik take readers into the marshes, bogs, waterways, and swamps these people's efforts have brought back to life. Howard's storytelling introduces grassroots conservators dedicated to learning through failure and persistence, to heeding the lessons taught by wetlands, to undertaking hard work inspired by the necessity of flood abatement or a desire to reconnect with the earth. Zalaznik's stunning black and white photos illuminate changes in the land and the people themselves. Seeds sprout after lying dormant for one hundred years. Water winds through ancient channels. Animals and native plants return. As the forgiving spirit of a wetland emerges, it nurtures a renewed landscape that alters our view of the environment and the planet. An inspiring document of passion and advocacy, In the Spirit of Wetlands reveals the transformative power of restoration"--